THE EFFECT OF SMOKING BEHAVIOR ON HEALTH EXPENDITURE IN INDONESIA’S RURAL AREAS - Firmansyah, Cyril Anfasha; Renaldi, Reza Galih; Monikka, Dinda; Sihaloho, Estro Dariatno (Jurnal Ekonomi Kesehatan Indonesia, 2022)
Smoking is one of the biggest causes of death in the world. The WHO reported that smoking kills 8 million people each year. Besides threatening global health, smoking by rural people tends to detain poverty alleviation efforts due to several factors, including cigarette expenditures and health expenditures. Indonesia has one of the most significant worldwide smoking prevalence and has become one of the countries that most suffer from smoking. The MoH Indonesia reported that health costs due to smoking reached Rp596.61 trillion in 2015. Previous studies found that smoking caused an increase in health expenditure due to smoking-related diseases in Indonesia. However, there is a lack of evidence found in rural areas. This research aims to answer whether smoking affects health expenditure in rural areas. Robust regression analysis is used in this model and processed by STATA 14 application. Using IFLS 5 data, the analysis shows that cigarettes consumed in rural areas have a positive and significant effect on outpatient costs. Increased outpatient costs in rural areas due to smoking will make the rural economy suffer and escalate poverty. The government should intensify the tobacco control policy in rural areas to avoid an increase of poverty rate in Indonesia.